2008
DOI: 10.1623/hysj.53.4.834
|View full text |Cite
|
Sign up to set email alerts
|

The impact of agricultural land use on stream chemistry and inputs to an inland reservoir: case of the Sauce Grande River, Argentina

Abstract: Water quality in the Paso Piedras Reservoir has deteriorated, primarily due to periodic blue-green algal blooms, making it temporarily unfit for human consumption. This phenomenon results from the eutrophication of waters of the watershed, and nutrients are considered to be the primary contributors to degradation of freshwater quality. In order to reduce the levels of nitrogen and, most of all, phosphorus, entering the Paso Piedras Reservoir, it is necessary to understand the incidence of diffuse transfers of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
(7 reference statements)
1
5
0
1
Order By: Relevance
“…The increasing TSI values might indicate that the river is becoming eutrophic downstream. The oligotrophic conditions found in the upper basin agree with the data previously recorded by Orioli et al (2008). Chla presented a gradual increase along the river, down to the Sauce Grande shallow lake (73.6 µg L − 1 at S10).…”
Section: Land Uses and Physicochemical Water Characteristicssupporting
confidence: 90%
See 1 more Smart Citation
“…The increasing TSI values might indicate that the river is becoming eutrophic downstream. The oligotrophic conditions found in the upper basin agree with the data previously recorded by Orioli et al (2008). Chla presented a gradual increase along the river, down to the Sauce Grande shallow lake (73.6 µg L − 1 at S10).…”
Section: Land Uses and Physicochemical Water Characteristicssupporting
confidence: 90%
“…Anthropogenic activities, such as agricultural activities and domestic dumping, might also contribute to an increase in the seston and OM concentrations. The differences in land use between sites could be responsible for the spatial changes (Orioli et al 2008), as observed here. These results are similar to those found in a river basin in Vietnam (Strady et al 2017) with untreated wastewater combined with industrial water.…”
Section: Land Uses and Physicochemical Water Characteristicsmentioning
confidence: 64%
“…In conclusion, increased turbidity is a major problem for lotic systems worldwide (Mol & Ouboter, 2004;Li et al, 2008;Orioli et al, 2008), yet little is known about its direct effects on foraging success and biotic interactions in stream organisms. We have demonstrated that increases in turbidity and velocity along with increased competition significantly reduce the foraging success of rosyside dace and the invasive yellowfin shiner.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that the most frequent cause of habitat degradation in streams is increased fine sediment loads, and these increases have been linked to changes in native aquatic communities in both the northern (Berkman & Rabeni, 1987) and southern hemispheres (Quinn et al, 1992;Richardson & Jowett (2002); Rowe et al, 2003;Townsend et al, 2004). Although ecosystems and species differ with geography, the anthropogenic causes of increased sedimentation in stream sediment are similar worldwide (Harding et al, 1999;Li et al, 2008; Correspondence: Gary D. Grossman, Warnell School of Forestry and Natural Resources, University of Georgia, Athens, GA 30602, U.S.A. E-mail: grossman@uga.edu Freshwater Biology (2009) 54, 1977-1989doi:10.1111/j.1365-2427.02248.x Ó 2009 Blackwell Publishing Ltd Orioli et al, 2008), including inappropriate agricultural, mining and forestry practices and urbanisation (Brasington & Richards, 2000;Mol & Ouboter, 2004;Bonnet, Ferreira & Lobo, 2008). Fine sediments may negatively affect stream biota through a variety of mechanisms, including (i) interference with migration behaviour (Richardson, Rowe & Smith, 2001), (ii) reduction of reproductive success (Burkhead & Jelks, 2001), (iii) increased vulnerability to predation (Miner & Stein, 1996), (iv) direct physiological damage (Berkman & Rabeni, 1987;Sutherland & Meyer, 2007), (v) reduced foraging success (Berkman & Rabeni, 1987;Rowe & Dean, 1998;Suttle et al, 2004) and (vi) reduced prey availability (Stuart-Smith, Richardson & White, 2004;Rabeni, Doisy & Zweig, 2005;White & Harvey, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Amongst the most evident anthropogenic pollution sources are the discharges of agricultural, industrial and urban wastewaters as well as the diffuse run-off of agri-chemicals from agricultural lands. [1][2][3][4] As a result, eutrophication (the biological response to the excess input of nutrients into a water-body) which was originally a natural slow process have been greatly enhanced by human activities. 5 Eutrophic aquatic ecosystems are typically characterised by, besides high nutrients loads, the recurrent occurrence of algal blooms and the associated strong depletion of dissolved oxygen which, in turn, strongly affects the other biological communities (aquatic ecosystems presenting low nutrients loads and low algal biomass are classified as oligotrophic, while mesotrophic aquatic ecosystems have intermediate characteristics).…”
Section: Introductionmentioning
confidence: 99%